2014
DOI: 10.1039/c3ta14441k
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and improved electrochemical performance of SiCN–graphene composite derived from poly(silylcarbondiimide) as Li-ion battery anode

Abstract: A SiCN-graphene nanocomposite anode material is designed and synthesized by the insertion of graphene sheets into the ceramic network of silicon carbonitride for the development of structurally and electrochemically stable lithium ion batteries. SiCN-graphene composite synthesis was achieved through controlled pyrolysis of poly(silylcarbondiimide)-derived SiCN on graphene surfaces that resulted in formation of a graphene supported ceramic SiCN-graphene architecture, in which graphene works as the layered base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 43 publications
4
39
0
Order By: Relevance
“…Stable capacity of ∼700 mAh g −1 electrode was observed at 100 mA g −1 electrode which decreased to ∼100 mAh g −1 electrode at 2,400 mA g −1 electrode and showed complete recovery when the current density was brought back to 100 mA g −1 electrode . Such stable performance is rarely reported for precursor-derived ceramic materials even on traditionally prepared electrode on copper foil where the current density and capacity are reported with respect to the active material only 46 47 48 . Tests were also conducted on 80SiOC specimen to ascertain if the charge capacity of the freestanding paper-based electrodes can be improved even further due to higher SiOC content.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Stable capacity of ∼700 mAh g −1 electrode was observed at 100 mA g −1 electrode which decreased to ∼100 mAh g −1 electrode at 2,400 mA g −1 electrode and showed complete recovery when the current density was brought back to 100 mA g −1 electrode . Such stable performance is rarely reported for precursor-derived ceramic materials even on traditionally prepared electrode on copper foil where the current density and capacity are reported with respect to the active material only 46 47 48 . Tests were also conducted on 80SiOC specimen to ascertain if the charge capacity of the freestanding paper-based electrodes can be improved even further due to higher SiOC content.…”
Section: Resultsmentioning
confidence: 93%
“…Continued search for better anodes has brought attention to unique, rarely studied molecular precursor-derived Si-based glass-ceramics (such as silicon oxycarbide or SiOC and silicon carbonitride or SiCN) materials 40 41 42 43 44 45 46 47 48 49 50 . SiOC is a high-temperature glass-ceramic with an open polymer-like network structure consisting of two interpenetrating amorphous phases of SiOC (Si bonded to O and C) and disordered carbon 42 .…”
mentioning
confidence: 99%
“…It was found that R 2 and R 3 were due to the solid electrolyte interface impedance and to the charge transfer resistance, respectively. Moreover, the liner part of the plot is likely due to the lithium diffusion in the 3D porous network 46 51 . The semicircle diameter of the SnO 2 -rGA-20 was smaller than that of SnO 2 -rGA-10, implying that the prepared electrodes were stable during charge/discharge cycles 52 .…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19] For example, SiCN-graphene composite anodes were fabricated, in which graphene sheets were inset in the ceramic network of SiCN. 20 The SiCN-graphene composite anodes showed a stable charge-discharge capacity. However, it still remains to be a challenge for uniformly integrating graphene into PDCs without aggregation.…”
Section: Introductionmentioning
confidence: 96%
“…There has been interest in integrating graphene in PDCs to alter their physical properties . For example, SiCN‐graphene composite anodes were fabricated, in which graphene sheets were inset in the ceramic network of SiCN . The SiCN‐graphene composite anodes showed a stable charge‐discharge capacity.…”
Section: Introductionmentioning
confidence: 99%